A multinomial logit model of college stopout and dropout behavior - Leslie Sundt Stratton; Dennis M. O'Toole; James N. Wetzel (Institute for the Study of Labor (IZA), 2005)
Studies of college attrition typically assume that all attrition is permanent. We use data from the 1990/94 Beginning Postsecondary Survey to distinguish between long-term dropout and short-term stopout behavior in order to test that assumption. We find significant differences between those who stop out and those who drop out in the first year. Failure to recognize these differences biases the results of standard attrition models and hence may cause policy makers to pursue inappropriate policy initiatives or incorrectly target at-risk populations. Furthermore, the type of financial aid received is found to have a differential impact on stopout versus dropout probabilities.
Keywords: I21; 330; college persistence; college dropout